(untitled) (Gumilyov Journal of Pedagogy, 2026)
The impact of emotional intelligence (EI) is currently being explored across diverse scientific fields, including education, psychology, and even robotics. In the information age, key competencies such as self-awareness, motivation for achievement, effective communication, and the ability to learn a foreign language have become increasingly important. Successful language learners are distinguished not only by cognitive abilities but also by motivational traits, including a positive task orientation, perseverance, a desire for success, and a tolerance for ambiguity. Emotional intelligence is therefore considered one of the most significant components of the educational process, influencing personal development, learning outcomes, and the formation of intercultural communicative competence. The purpose of this research is to analyze scientific literature on EI, examine its impact on foreign language acquisition, and determine its role in developing students’ intercultural communicative competence. Students’ emotional intelligence was assessed using N. Hall’s methodology, which consists of five scales and thirty items. The article also describes elicitation techniques, cognitive and socio-affective strategies, and other methodological approaches used in the development of EI within foreign language teaching. The results demonstrate that emotional intelligence has a positive influence on students’ motivation and foreign language learning, supporting the integration of EI development into modern language education.